2008
DOI: 10.1111/j.1523-1739.2008.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Risk of Habitat Conversion in Native Temperate Grasslands

Abstract: Native grasslands that support diverse populations of birds are being converted to cropland at an increasing rate in the Prairie Pothole Region of North America. Although limited funding is currently available to mitigate losses, accurate predictions of probability of conversion would increase the efficiency of conservation measures. We studied conversion of native grassland to cropland in the Missouri Coteau region of North and South Dakota (U.S.A.) during 1989-2003. We estimated the probability of conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 31 publications
(37 reference statements)
2
86
2
Order By: Relevance
“…Furthermore, our analysis revealed how grassland land covers that beekeepers target when selecting commercial apiary sites are becoming less common in portions of central and eastern ND and SD, changes that may have lasting impact on pollinator services and conservation efforts. Although past research has shown land-use changes occurring in portions of the Central and Northern Plains (22,29), our study models large-scale land-use changes from the perspective of the honey bee-keeping industry. Specifically, we used land-use data collected from >18,000 registered apiary locations to derive our spatial models, thereby providing a realistic depiction of how recent land-use changes have affected habitat and foraging area across two states that supported 770,000 colonies in 2014 (17).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our analysis revealed how grassland land covers that beekeepers target when selecting commercial apiary sites are becoming less common in portions of central and eastern ND and SD, changes that may have lasting impact on pollinator services and conservation efforts. Although past research has shown land-use changes occurring in portions of the Central and Northern Plains (22,29), our study models large-scale land-use changes from the perspective of the honey bee-keeping industry. Specifically, we used land-use data collected from >18,000 registered apiary locations to derive our spatial models, thereby providing a realistic depiction of how recent land-use changes have affected habitat and foraging area across two states that supported 770,000 colonies in 2014 (17).…”
Section: Discussionmentioning
confidence: 99%
“…agriculture | Great Plains | land capability | land cover change H igh corn and soybean prices, prompted largely by demand for biofuel feedstocks, are driving one of the most important land cover/land use change (LCLUC) events in recent US history; the accelerated conversion of grassland to cropland in the US Corn Belt (1)(2)(3)(4)(5). Likely impacts of such conversion include a reduction in bird diversity across the region (6) and accruement of a significant carbon debt (7).…”
mentioning
confidence: 99%
“…Meanwhile, regional-scale studies of grassland conversion have been based on agricultural production statistics aggregated at the county level (3,4), precluding largearea geospatial analysis of grassland conversion at farm to subcounty scales. Finally, most studies of grassland conversion (1)(2)(3) precede the doubling of corn and soybean prices between 2006 and 2011 (13), with the exception of one (4). From 2006 to 2008, the corn and soybean area harvested in the United States increased by more than 3.2 million ha (4).…”
mentioning
confidence: 99%
“…One study, however, found that conversion rates in the prairie potholes region of the United States exceed tropical rainforest conversion rates. 4 Although an argument could be made for excluding precompliant ranchers from participating in carbon markets in order to maintain legitimacy in the marketplace, there are a number of implications associated with such a strict definition that policymakers will need to consider. First, if these ranchers-often the opinion leaders in their communitiesare excluded, it could be harder to engage the more mainstream ranchers who look to the good stewards and innovators in their communities for guidance.…”
Section: The Legitimacy Problem: Additionality Concerns When Ranchersmentioning
confidence: 99%